Structure of the Oxidized Form of a Flavodoxin at 2.5-Å Resolution: Resolution of the Phase Ambiguity by Anomalous Scattering - Watenpaugh, K. D. (1972)
Flavodoxin from Desulfovibrio vulgaris crystallizes in the oxidized form as well-formed, tetragonal bipyramids, space group P4(3)2(1)2, unit-cell parameters, a = b = 51.6 Å, c = 139.6 Å, 8 molecules per unit cell. The structure has been determined at 2.5-Å resolution with phases based on a single isomorphous derivative. The phase ambiguity of a single derivative was resolved by use of anomalous scattering from the single-site Sm(+3). The molecule has a five-strand pleated sheet core with two long helices on either side of the sheet. The flavin mononucleotide lies mostly buried on one side of the molecule, but the methyl groups, one edge of the flavin, and part of the ribityl are exposed at the surface.